(untitled) (Global Journal of Science Frontier Research, 2014)
In this study, the bryophyte flora of the Biga Peninsula (Canakkale province) was investigated. In total 119 taxa were found in this area. According to the grid-square system formed by Henderson (1961), 37 moss taxa for A1 square are new records. Among them Rhabdoweisia crispata, Schistidium robustum and Scorpidium cossonii are recorded for the first time in Turkey. In addition Mielichhoferia elongata (Hoppe & Hornsch. ex Hook.) Hornsch. and Meesia uliginosa Hedw. were given as new records from the Thrace region for Turkey. And also all new national records are described and illustrated. Diagnostic characters, a description, detailed illustrations and taxonomic comments on the species are given. It is compared with the related species and the geographic distributions of the new records are given.